Optimal path planning of a cable-suspended robot with moving boundary using optimal feedback linearization approach - Korayem, M. H.; Tourajizadeh, H.; Zehfroosh, A.; Korayem, A. H. (Nonlinear dynamics, 2014)
In this paper, the optimal path of a cable-suspended robot between two boundaries is assessed subject to its maximum load, while the initial and target points are moving boundary. Considering the fact that the most important application of cable robots is load carrying between two boundaries, planning the optimal path in which the heaviest load can be carried is extremely applicable. A closed loop optimal path planning algorithm is proposed in this paper for non-linear dynamic of a cable robots based on optimal feedback linearization. This method not only produces the optimal path of the end-effector, but also is robust to external disturbances and parametric uncertainties as a result of its closed loop nature. Moreover, considering the fact that in many automation applications the target of load handling is a sort of moving boundary like conveyors, finding the optimal point of this boundary which produces the optimal path with the maximum dynamic load carrying capacity (DLCC) amongst the other points of the boundary is obviously a useful study. Therefore, an online solution, based on variational algorithm is proposed here to solve the moving boundary problem which is compatible with the presented closed loop optimal path planning. This method is developed for both the initial and final moving boundaries. Finally maximum DLCC is obtained using an iterative method to check the optimality of the proposed method. The efficiency of the proposed algorithm is verified at the end by the aid of some simulation scenarios performed on a spatial six DOFs cable robot with six cables. The motors’ torque, motors’ speed, and resultant DLCCs are calculated for both simple optimal path and moving boundary cases and comparison of the results proves the mentioned claims based on superiority of the proposed algorithm of moving boundary in saving the energy and increasing the DLCC. All simulation results are supported by conducting an experimental study on the cable robot of IUST (ICaSbot) for regulation movement of the end-effector with moving boundary.